ä½¿ç”¨ç¬”ç”»ç¬”é¡ºæ•™å¦æé«˜å›½ç«‹åˆä¸ç¬¬åå¦æ ¡å¦ç”Ÿçš„æ±‰å—ä¹¦å†™èƒ½åŠ› - Andika, Andika; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractChinese letters have important role in teaching chinese language, and it is also difficult. In teaching and learning proses, the students face many difficulties. This is caused by the differences between Indonesian Language and Chinese language. Indonesian Language uses the alphabet as its letters while Chinese uses scratches/lines and the rule of scratch. The students of Junior High School No. 10 Pontianak (SMPN 10 Pontianak) also had many difficulties in learning Chinese Language. From that problems, the researcher chose the school as the subject to conduct the research using the method of teaching Chinese scratches and its rules.The result of the research shows that percentage of writing Chinese letter had improved. Before the treatment, the percentage of teaching was only 43%, and after the treatment the improvement increased to 63%. This result of the research proves that the method used in this research improves the students' ability in writing Chinese letters. Keyword : Chinese letters, Scratch, The rule of scratch